Effect of Glass Wool Addition on Some Properties of Cement Mortar - Hussein Alaa Jaber (Engineering and Technology Journal, 2016)
This work presents an investigation of possible incorporation of the glass wool (fiberglass insulation) in cement mortar as an insulating building material. Mortar of ordinary Portland cement of (1:3) cement to sand ratio was mixed with glass wool at different weight percentages ranged between (0 – 0.24) wt%. Density, water absorption, thermal conductivity, compressive strength and flexural strength experimentally were investigated for mortar specimens after curing for (28 days). The results showed that the incorporation of glass wool decreases the density, thermal conductivity and compressive strength, but the flexural strength of cement mortar enhances. Thermal conductivity of the cement mortar has decreased by about 44 % by increasing of glass wool content up to 0.24 wt%. Thus, utilization of glass wool as constituents in cement mortar appears to be a promising opportunity that enables applying as thermal insulation materials in constructions.